(untitled) (Linguist, 2021)
The Arabic linguistic literature has known in its history two distinct types of scientific works: authentic authorship attributed explicitly to specific authors and works translated from foreign languages to Arabic. There is no doubt that each of these two types has its own criteria governing its value, quality and the scientific context is still in need of more serious mixing achievements in both directions. This paper aims to reveal a hybrid and dangerous type of works that has begun to invade the field of Arabic linguistics characterized by deliberate and planned mixing of original authorship and translation. This has produced for us what might be called: "an authorship that is more like a translation, or a translation which is more like an authorship". Salah Fadl’s book: "Stylistics: its Principles and Practice/ Ilm el-Uslob: Mabadi’uhu wa Ijra’atuhu" and also in most of his other works are a well-represented model of this hybrid genre. This paper is an attempt to unveil elusive techniques he commits to achieve his scientifically and ethically illegal goal.